2016
DOI: 10.1080/10826068.2016.1224247
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical properties and evaluation of washing performance in commercial detergent compatibility of two collagenolytic serine peptidases secreted byAspergillus fischeriandPenicillium citrinum

Abstract: Filamentous fungi secrete diverse peptidases with different biochemical properties, which is of considerable importance for application in various commercial sectors. In this study, we describe the isolation of two fungal species collected from the soil of decayed organic matter: Aspergillus fischeri and Penicillium citrinum. In a submerged bioprocess, we observed better peptidase production with the fungus P. citrinum, which reached a peak production at 168 h with 760 U/mL, in comparison with the fungus A. fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Several studies have showed the production of serine peptidase from bacteria and fungi, for example, Silva et al [3] with Penicillium corylophilum and Penicillium waksmanii, Silva et al [29] and Silva et al [4] with A. fumigatus, Graminho et al [30] with P. waksmanii, Biaggio et al [15] with A. terreus, Ida et al [31] with Aspergillus fischeri and Penicillium citrinum, a thermostable peptidase from Geobacillus stearothermophilus [32], alkaline serine peptidase from Bacillus lehensis [33], subtilisin from B. licheniformis and Bacillus amyloliquefaciens [24], and keratinases from Chryseobacterium L99 sp. nov. [34] and Bacillus halodurans PPKS-2 [35].…”
Section: Serine Peptidasementioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have showed the production of serine peptidase from bacteria and fungi, for example, Silva et al [3] with Penicillium corylophilum and Penicillium waksmanii, Silva et al [29] and Silva et al [4] with A. fumigatus, Graminho et al [30] with P. waksmanii, Biaggio et al [15] with A. terreus, Ida et al [31] with Aspergillus fischeri and Penicillium citrinum, a thermostable peptidase from Geobacillus stearothermophilus [32], alkaline serine peptidase from Bacillus lehensis [33], subtilisin from B. licheniformis and Bacillus amyloliquefaciens [24], and keratinases from Chryseobacterium L99 sp. nov. [34] and Bacillus halodurans PPKS-2 [35].…”
Section: Serine Peptidasementioning
confidence: 99%
“…The use of peptidase as additives in detergent composition accounts for the largest commercial use of these enzymes. This application is due to activity and stability at alkaline pH and the formulation of detergents, as well as its action in a wide variety of protein substrates [10,31,67]. Currently, subtilisin from Bacillus species has been explored for application in detergent formulation [2].…”
Section: Other Commercial Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzymes enhance the efficacy of detergents for removing proteins from cloths soiled with sweat, grass, milk, egg, blood, etc. (Ida et al 2016). Proteases are the most extensively used enzymes in detergent formulations; however, amylases and lipases are also being added.…”
Section: Proteases In Detergent Industrymentioning
confidence: 99%
“…Despite the fact that among microorganisms producing protease and collagenase bacteria, fungi, yeast and actinomycetes are noted, micromycetes have recently become widespread due to the ease of their cultivation and high productivity. The preparations from micromycetes of the genus Aspergillus, Penicillium, and others are successfully used [13][14][15].…”
mentioning
confidence: 99%